2022
DOI: 10.3389/fmats.2022.994265
|View full text |Cite
|
Sign up to set email alerts
|

Application of chitosan-based materials in surgical or postoperative hemostasis

Abstract: Uncontrolled bleeding from trauma or surgery remains an important factor affecting the survival and prognosis of surgical patients. Failure to timeously stop bleeding will not only prolong the operative time but also threaten the patient’s life. Timely hemostasis after bleeding has become the most concerned event for surgeons. At present, the most commonly used hemostasis methods in the operating room include ligation of blood vessels, electrocautery, and gauze compression to stop bleeding. However, These hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…Excessive bleeding, in fact, can be responsible for large blood losses, which require timely transfusions of blood or blood products, exposing the patient to immunological, infectious and immunosuppressive complications [64,65]. Preventing excessive blood loss during surgery is equivalent to significantly reducing the risk of perioperative complications and surgical reoperation, thus reducing hospital stays and hospitalization costs [66,67]. In a study conducted by Pappas et al on venous and/or arterial femoral sheaths undergoing elective percutaneous diagnostic or therapeutic procedures, it was shown that the use of the HemCon patch successfully reduced patients' waiting time and hospital stay by promoting patients' ambulation four hours after surgery without complications [68].…”
Section: Surgical Applications Of Chitosan Dressingsmentioning
confidence: 99%
“…Excessive bleeding, in fact, can be responsible for large blood losses, which require timely transfusions of blood or blood products, exposing the patient to immunological, infectious and immunosuppressive complications [64,65]. Preventing excessive blood loss during surgery is equivalent to significantly reducing the risk of perioperative complications and surgical reoperation, thus reducing hospital stays and hospitalization costs [66,67]. In a study conducted by Pappas et al on venous and/or arterial femoral sheaths undergoing elective percutaneous diagnostic or therapeutic procedures, it was shown that the use of the HemCon patch successfully reduced patients' waiting time and hospital stay by promoting patients' ambulation four hours after surgery without complications [68].…”
Section: Surgical Applications Of Chitosan Dressingsmentioning
confidence: 99%
“…Dead MSCs release toxic substances that exacerbate SCI damage (143). The survival rate and long-term survival of MSCs in hostile environments remain unresolved issues (144). Gels and scaffolds based on stem cell therapy can deliver MSCs to the site of injury and release MSCs slowly and continuously to the site of injury (145)(146)(147)(148)(149).…”
Section: Challenges In the Clinical Application Of Msc Therapymentioning
confidence: 99%
“…Under acidic conditions, chitosan has the capacity to trigger the coagulation of proteins. These coagulated protein clusters wield the potential to disrupt the integrity of the bacterial cell membrane, hamper the microorganism’s metabolic functions, or even culminate in cell lysis [ 143 ]. Furthermore, the aggregation of coagulated proteins can give rise to a barricade that obstructs bacteria from accessing essential nutrients or expelling waste products.…”
Section: Antibacterial Activity Of Chitosan and Its Derivativesmentioning
confidence: 99%